Eurasian Business and Economics Perspectives Proceedings of the 36th Eurasia Business and Economics Society Conference - Bilgin, Mehmet Huseyin; Danis, Hakan; Demir, Ender; Bodolica, Virginia (Cham : Springer International Publishing : Imprint: Springer, 2022)
EBES conferences have been intellectual hub for academic discussion in economics, finance, and business fields and provide network opportunities for participants to make long lasting academic cooperation. This is the 23rd volume of the Eurasian Studies in Business and Economics (EBES's official proceeding series) which includes selected papers from the 36th EBES Conference - Istanbul. The conference was organized on July 1-3, 2021 in hybrid mode with both online and in-person presentation. In the conference, 141 papers by 311 colleagues from 49 countries were presented. Both theoretical and empirical papers in this volume cover diverse areas of business, economics, and finance from many different regions. Therefore, it provides a great opportunity to colleagues, professionals, and students to catch up with the most recent studies in different fields and empirical findings on many countries and regions.
Part 1. Eurasian Business Perspectives: Education -- Chapter 1. Understanding Student Learning Gain: Using Student-staff Partnerships Within Higher Education to Inform the Continuous Improvement Process -- Chapter 2. The Role of Technology in Student Learning and Engagement: The Case of the Webinar -- Chapter 3. Investigation of Higher Education Teacher Adoption of Microsoft Teams: Managing Behaviour Through Online Delivery and Promoting Positive Usage -- Part 2. Eurasian Business Perspectives: Entrepreneurship -- Chapter 4. Driving Economic Growth: Examining the Role of Leadership Within SME Innovation -- Chapter 5. It's Not Just Physical: Gender and Bias in Equity Crowdfunding -- Part 3. Eurasian Business Perspectives: Management -- Chapter 6. Development of Organizational Trust Questionnaire -- Chapter 7. Specific Factors Influencing Patient Satisfaction in Swiss Ophthalmology Private Practice -- Part 4. Eurasian Business Perspectives: Tourism -- Chapter 8. An Evaluation of Green Certification Program: A Study of Two Island Resorts in Malaysia and Indonesia -- Chapter 9. The Impact of Employees' absorptive Capacity on Digital Transformation of Tourism and Travel Services: Evidience from the Egyptiant Travel Agencies -- Part 5. Eurasian Economic Perspectives: Accounting & Finance -- Chapter 10. Use of Management Accounting Techniques in Croatian Manufacturing Companies -- Chapter 11. Intellectual Capital and Corporate Risk Disclosure in the Nigerian Banking Sector -- Chapter 12. Bibliometric Analysis of Green Bonds -- Chapter 13. Basel III and Firm Performance: A Lens of Managerial Ownership -- Part 6. Eurasian Economic Perspectives: Growth & Development -- Chapter 14. Research Trends in the Field of Islamic Social Finance -- Chapter 15. Return Migration as a Driver of Regional Development: A Case of North-east Estonia -- Chapter 16. Financing Sustainable Economic Growth: Evidence from Europe -- Part 7. Eurasian Economic Perspectives: Regional Studies -- Chapter 17. A Comparative Analysis on the Bureaucratic Process in Establishing Health Cooperatives: The Cases of Turkey and the United Kingdom -- Chapter 18. Structural Analysis of the Cultural - Creative Industries of Romanian Creative Cities.
Keywords: Management; Macroeconomics; Industries; Regional economics; Spatial economics; Management; Macroeconomics and Monetary Economics; Industries; Regional and Spatial Economics